Peningkatan Hasil Belajar Siswa Kelas 2 Materi Pengukuran Waktu Menggunakan Model Problem Based Learning di SDN Gayam 1 dengan Media Jam Analog - Aprilia Novitasari; Kharisma Eka Putri; Novi Rochmawati (Jurnal Simki Postgraduate, 2025)
This study aims to analyze the improvement of student learning outcomes in the Time Measurement material by implementing the Problem Based Learning learning model in class II of SDN Gayam 1. This study uses the Classroom Action Research (CAR) method which is carried out for one month, precisely in February 2025 in two cycles. Each cycle consists of the planning stage, action implementation, observation, and reflection. Data collection techniques through teacher and student observations and documentation of learning outcomes, then analyzed using the percentage method. In cycle I, learning using video learning media has increased compared to the previous cycle. However, the level of completion is still not optimal, namely only 24 students or 74.8% reached the KKM. To overcome this, in cycle II, the study used analog clock media as a tool in the learning process. The evaluation results showed that the use of analog clock media increased student learning outcomes by 99.8% or 28 students completed. So it can be concluded that the PBL model supported by the use of analog clock media has succeeded in significantly improving student learning outcomes.